2011
DOI: 10.1111/j.1438-8677.2011.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PGPR inoculation on growth and antioxidant status of wheat under saline conditions

Abstract: Two plant growth-promoting rhizobacterial (PGPR) strains, Bacillus subtilis SU47 and Arthrobacter sp. SU18, were found to tolerate 8% NaCl. Wheat co-inoculated with these two PGPR strains, and grown under different salinity regimes (2-6 dS m(-1) ), showed an increase in dry biomass, total soluble sugars and proline content. Wheat sodium content was reduced under co-inoculated conditions but not after single inoculation with either strain or in the control. The activity of antioxidant enzymes in wheat leaves de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
136
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(159 citation statements)
references
References 44 publications
19
136
0
4
Order By: Relevance
“…In a follow-up study, Upadhyay et al investigated the effects of two salt-tolerant PGPR (B. subtilis and Arthobacter sp.) on wheat plants under different salinity regimes and the results obtained demonstrated alleviation of the salinity stress effects on plants treated with bacteria [97]. Similar outcome has been reported by Nia et al for Azospirillum strains on wheat plants [144].…”
Section: Salinitysupporting
confidence: 88%
See 2 more Smart Citations
“…In a follow-up study, Upadhyay et al investigated the effects of two salt-tolerant PGPR (B. subtilis and Arthobacter sp.) on wheat plants under different salinity regimes and the results obtained demonstrated alleviation of the salinity stress effects on plants treated with bacteria [97]. Similar outcome has been reported by Nia et al for Azospirillum strains on wheat plants [144].…”
Section: Salinitysupporting
confidence: 88%
“…PGPRs have been demonstrated to enhance wheat stress tolerance via osmolyte accumulation as reported in Refs. [95][96][97]. Ali et al used P. putida AKMP7 resulting in significant increase in proline levels in heat-stressed wheat plants [98].…”
Section: Accumulation Of Osmolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan et al (2017) reported that the combined application of PGPR lead to significant decrease in CAT, POD and SOD activities in the leaves of chickpea grown under stress conditont. Reduction in antioxidant enzymes activity by PGPR or PGR had been reported previously (Upadhyay et al 2012;Mahsa Hosseini et al 2015).…”
Section: Discussionsupporting
confidence: 65%
“…+ silicon nanoparticles) treatment at the salinity levels of 0.3, 4, and 6 dS m -1 , S.E.N and S.E.B.N treatments at the salinity level of 8 dS m -1 could also significantly decrease the catalase activity compared to the control sample. These findings are in line with Upadhyay et al [51], who reported that bacteria could affect soil particle distribution around the roots by producing EPS and improving water availability to the considered plants and lead to decreasing the catalase activity despite saline conditions. The results of Baniaghil et al [52] indicated a significant increase in the activity of catalase enzymes in corn under salt stress and the positive effect of bacterial inoculation on reduced oxidative damage caused by salt stress, which confirms the results of the present study.…”
Section: Plant Biomasssupporting
confidence: 91%